(untitled) (Tempo e Argumento, 2024)
On February 9, 1914, the ideal of an egalitarian society, represented by the Holy Brotherhood of monks José and João Maria, was interrupted by the bombing of the Holy City of Taquaruçu, led by an alliance of coronels, politicians, and military men from Santa Catarina, southern Brazil. Almost a century later, this societal project resurfaced through the cultural group Renascença Cabocla, founded by descendants of the monks’ devotees. This article investigates the continuity of the Brotherhood’s religious and social values over time, highlighting Taquaruçu’s role in the memory of the conflict known as the Contestado War and how the group Renascença Cabocla keeps these ideals alive in the present. Based on theoretical discussions about history of the present time and influenced by Gilles Deleuze’s concept of temporality, this study proposes a reflection on the coexistence between the past and the present. Thus, it identifies in the ideal of the Holy Brotherhood, briefly lived in Taquaruçu, and in the group Renascença an ‘extended and sacred time’ that transcends linear chronology. This approach suggests a review of the historical temporality that guides history of the present time, introducing the notion of an ‘eternal time’ — a continuous and expansive present, as formulated by Deleuze when discussing the event’s structure between the times of Cronos and Aion. In this way, it proposes an expansion of the conception of historical time that guides, as a rule, the temporal notion that serves as the epistemological basis for history of the present time, as it has been debated and practiced today.